Investigation on Seismic Behavior of Historical Tokatlı Bridge under Near-Fault Earthquakes - Memduh Karalar; Mustafa Yeşil (Advances in Civil Engineering)
The main purpose of this study is to compare the static and dynamic behavior of a historical single-span masonry arch bridge under different near-fault earthquakes. The historical Tokatlı Bridge, built in Karabük, is chosen for this study. To investigate the behavior of near-fault earthquakes on the historical masonry bridge, first, a finite element model is built and analyzed under various near-fault earthquakes by using ANSYS and SAP2000. To build a finite element model, 162920 nodes and 47818 elements are used in ANSYS. First, finite element analysis results are compared to each other under Earth gravity. Then, ground motions near the fault are chosen to be used in this study. These earthquakes can be listed as follows: Cape Mend (1992), Kobe (1995), Superstition Hills (1987), Northridge (1994), Imperial Valley (1979), and Chi-Chi (1999). The behavior of the single-span historical bridge is obtained under these ground motions, and the results are compared with each other using contour diagrams using ANSYS. Furthermore, at the end of these analyses, it is observed that the tensile stresses have reached the permissible masonry tensile strength, especially on the upper side of the large belt, on the upper side of the belt, and on the side of the belt, and pose a risk for damage.